Implementasi Perda Inisiatif Dewan Perwakilan Rakyat Daerah Kota Bukittinggi Perspektif Fiqh Siyāsah - Refliandi, Irvan (Yayasan Lembaga Studi Makwa, 2022)
The background of this research is when the Bukittinggi’s DPRD has not carried out its performance in accordance with the expectations and wishes of the people, as is the case when the number of regional regulations produced by the legislature is less than the number of regional regulations originating from the executive. This study aims to find out how the implementation of the Initiative regional regulation in the Bukittinggi’s DPRD environment and what factors became obstacles in the formation of the initiative for regional regulation of the Bukittinggi’s DPRD. The type of research that the authors used in this study was field research conducted in Bukittinggi. Primary data sources are obtained through interviews, observation and documentation of related stakeholders. Based on the results of the research, it can be seen that the implementation of the regional regulation initiated by the Bukitinggi’s DPRD has not gone well because there are still several obstacles, such as low human resources, lack of socialization of the Perda formation program and changes in community dynamics.